324PA novel anti-PD-1 antibody HLX10 study led to the initiation of combination immunotherapy. (24th November 2019) - Chao, T Y; Ho, C L; Cheng, W H; Chang, C L; Hsieh, Y Y; Jiang, W; Liu, S; Luk, A; Lin, S F; Hsieh, T C; Liu, E
Abstract: Background: HLX10, a fully humanized IgG4 monoclonal antibody against the programmed death-1 (PD-1) receptor blocking PD-1, increased functional activities of human T-cells and showed in-vitro antitumour activity in xenograft models. The combined inhibition of PD-1 and VEGFR pathways may enhance a sustained suppression of cancer-related angiogenesis and tumour growth. Here, we present the phase 1 study data of HLX10 and the development of HLX10 as targeted combination immunotherapy. Methods: We conducted an open-label, dose-finding with Bayesian optimal interval adaptive design study to evaluate safety, maximum tolerated dose, PK and clinical activity of HLX10 in patients with advanced or metastatic solid tumours refractory to standard therapy. Patients (pts) received biweekly i.v. infusions of HLX10 at doses of 0.3, 1, 3 and 10 mg/kg until disease progression, intolerable toxicities or withdrawal from the study. The dose-limiting toxicities were observed for 28 days after treatment. Clinical response was evaluated every 8 weeks for the first 24 weeks followed by every 12 weeks. Safety, PK and clinical response evaluations were performed throughout the study. Results: As of 27-June-2019, 16 pts were dosed with HLX10 at various doses and maintained >90% PD1 receptor occupancy on the peripheral T-cells. Among 13 pts being evaluated for efficacy, 2 pts each at 0.3 and 3 mg/kg cohorts achieved stable disease; 1 pt at 3 mg/kg cohort achieved partial response with the longest follow-up time of 220 days. No infusionrelated reaction or additional safety signal was observed up to 10 mg/kg. The PK profiles demonstrated dose proportional manner as shown in the table. Conclusions: HLX10 is well tolerated, shows promising antitumour activities with durable objective responses in various cancers, and exhibits similar PK results to pembrolizumab and nivolumab. HLX10 is currently being tested in the first China combo-immunotherapy studies with HLX04 (a bevacizumab biosimilar) in advanced solid tumours with the longest follow-up time of > 200 days as of 20-June-2019 and in first-line treatment of metastatic NSCLC. Clinical trial identification: HLX10-001(Registration Number: NCT0346875) monotherapy in advanced solid tumours; HLX10HLX04-001(Registration Number: NCT03757936) combo-immunotherapy in advanced solid tumours; HLX10-002-NSCLC301(Registration Number: NCT03952403) combo-immunotherapy in NSCLC. Legal entity responsible for the study: Shanghai Henlius Biotech, Inc; Taiwan Henlix Biotech., Co., LTD. Funding: Shanghai Henlius Biotech, Inc. Disclosure: T.Y. Chao: Research grant / Funding (institution): Taiwan Henlix Biotech., Co., LTD. C.L. Ho: Research grant / Funding (institution): Taiwan Henlix Biotech., Co., LTD. W.H. Cheng: Research grant / Funding (institution): Taiwan Henlix Biotech., Co., LTD. C.L. Chang: Research grant / Funding (institution): Taiwan Henlix Biotech., Co., LTD. Y.Y. Hsieh: Research grant / Funding (institution): Taiwan Henlix Biotech., Co., LTD. W. Jiang: Full / Part-time employment: Shanghai Henlius Biotech, Inc. S. Liu: Full / Part-time employment: Shanghai Henlius Biotech, Inc. A. LUK: Full / Part-time employment: Shanghai Henlius Biotech, Inc. S.F. Lin: Full / Part-time employment: Taiwan Henlix Biotech., Co., LTD. T.C. Hsieh: Full / Part-time employment: Taiwan Henlix Biotech., Co., LTD. E. Liu: Full / Part-time employment: Taiwan Henlix Biotech., Co., LTD.